The anti-inflammatory action of Curcuma longa L. as a herbal medicine: a literature review (Research, Society and Development, 2022)
Objective: To describe the anti-inflammatory action of Curcuma longa L. as a herbal medicine. Method: This is an                             integrative literature review, with a qualitative and exploratory approach, together with a database on the platforms SCIELO, BVS, LILACS, Ministry of Health (MS) and Google Scholar, with publications of scientific documents among the years from 2015 to 2022. Results: Curcumin is the property with the highest concentration in turmeric, since this component has sites of antioxidant, anti-inflammatory and antiapoptotic action, among other pharmacological activities. Inflammation is the body's defense mechanism against aggression, this process is a reflection of an attempt to combat aggression and restore hemostasis. Studies show that curcumin has a significant response in the anti-inflammatory action, acting especially in the inhibition of multiple pro-inflammatory pathways, decreasing the activities of the cytokines of this process. Conclusion: Therefore, systematic studies are needed about this property of acting in the inflammatory process as a safe and effective herbal therapeutic alternative.